Basic personal values in the midst of the COVID-19 pandemic in Italy: A two-wave longitudinal study - Michele Vecchione (PLoS ONE, 2022)
This study investigated value change during two phases of the COVID-19 pandemic in Italy, one of the most affected countries in the world. The first wave of data was collected in summer 2020, when the virus was on the retreat. The second wave was collected in autumn, at the peak of the second pandemic wave (November 2020). We investigated how Schwartz’s higher-order values changed over the two waves of the study, using economic condition as a predictor of change. We also examined whether value change predicted subsequent value-expressive behavior. Results showed no mean-level change for self-enhancement, self-transcendence, conservation, and openness to change values, but significant interindividual differences in the amount of change for each of the four values. Economic condition emerged as a significant predictor of change in conservation values: Individuals with a decreasing income since the beginning of the pandemic were more likely to increase the importance assigned to these values with respect to individuals whose economic well-being has remained unchanged. Moreover, an increase in conservation and openness to change values predicted behaviors that are mostly expressive of these values, above and beyond value importance at Time 1. Results and their implications for the study of values are discussed.